Muscle activity and the freestyle stroke cycle
The internal shoulder-joint rotators, the anterior deltoid, pectoralis major, and latissimus dorsi, and external humeral rotators, the infraspinatus, teres minor, andsupraspinatus, were studied. All muscles were active throughout the stroke, firing with different emphases at different stages. The external rotator group showed higheractivity. 1.The catch/outsweep phase of the stroke activated the muscles the least and produced a negative propulsive component. 2.During the insweep, the largest propulsive forces were created mainly through the pectoralis major, with some assistance from the infraspinatus and teres minor muscles. 3.In the finish phase, the latissimus dorsi was the primary contributor although the infraspinatus and teres minor muscles continued to fire as a means of protecting the shoulder joint. 4.The high firing of the external rotators during the stroke is probably linked to stabilization of the shoulder joint. Implication: These are the crucial muscles to be strengthened. [From what is known, the best methods for doing this are to overload the arms in swimming actions. Swimming arms only with the feet tied, and tethered swimming for power and stroke length are appropriate. These forms of power training should only be sustained as maintenance training in the specific preparatory, precompetition, and competition phases of training. Using hand paddles does not overload the shoulder muscles but rather decreases their work.]